2020
DOI: 10.15376/biores.15.2.4591-4635
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of alkyl chains of fatty acids in papermaking systems: A review of related pitch issues, hydrophobic sizing, and pH effects

Abstract: This review article considers the role of fatty acids and the mutual association of their long-chain (e.g. C18) alkyl and alkenyl groups in some important aspects of papermaking. In particular, published findings suggest that interactions involving fatty acids present as condensed monolayer films can play a controlling role in pitch deposition problems. Self-association among the tails of fatty acids and their soaps also helps to explain some puzzling aspects of hydrophobic sizing of paper. When fatty acids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…A tendency of the tail groups of surfactants to associate into tight films has been attributed to a hydrophobic effect (Tanford 1980;Hubbe et al 2020). The driving force for such association is the relatively high energy of hydrogen bond interactions in aqueous systems.…”
Section: Hydrophobic Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…A tendency of the tail groups of surfactants to associate into tight films has been attributed to a hydrophobic effect (Tanford 1980;Hubbe et al 2020). The driving force for such association is the relatively high energy of hydrogen bond interactions in aqueous systems.…”
Section: Hydrophobic Interactionsmentioning
confidence: 99%
“…When comparing the effects of different oily materials, researchers have found it advantageous to categorize compounds in terms of their equivalent alkane carbon numbers (EACN) (Phaodee et al 2020;Chen et al 2022). Thus, the presence of a carbon-carbon double bond within a linear alkyl chain often leads to properties equivalent to those of a saturated chain with two less carbons in it (Brito et al 2011;Hubbe et al 2020). The difference has been attributed to the poorer packing ability of the unsaturated alkyl chains.…”
Section: Equivalent Alkane Carbon Numbers For Oily Phasesmentioning
confidence: 99%
See 2 more Smart Citations
“…This showed that, as time increased, the dissolution rate of the triglyceride fats on the straw in the ionic liquid decreased slowly. According to the dissolution mechanism of the ionic liquid, the anions and cations in the ionic liquid directly acted on the triglyceride fats and broke bonds that held together mainly by van der Waals forces therein, thereby dissolving the triglyceride fats (Hubbe 2020). With regard to the dissolution of polysaccharides by ionic liquids, Remsing et al (2006) used a carbon tracer to confirm its occurrence when they studied the dissolution of cellulose by ionic liquids.…”
Section: Triglyceride Fatsmentioning
confidence: 99%